Influence of Casting Solvent and Polymer on Permeability of Propranolol Hydrochloride through Eudragit RL-100 and Eudragit RLPO Films - soujanya, Banavat; J, geethanjali; D, Mounika; V, sai kishore (Asian Journal of Pharmaceutical Research and Development, 2014)
In the present work, eudragitL100and eudragitRLPO films were prepared and evaluated as rate controlling membrane for transdermal drug delivery systems. Dibutyl phthalate or propylene glycol at a concentration of 15w/w of the polymer was used as a plasticizer in the preparation of eudragitL100and eudragitRLPO films. Casting on mercury surface technique was employed for preparation of eudragitL100and eudragitRLPO films. The dry films were evaluated for physical appearance, water vapour transmission, drug diffusion and permeability coefficient. Both watervapour transmissions, drug diffusion rate followed zero-order kinetics. The mechanism of drug release was governed by peppas model. The diffusion exponent of releaseprofiles (slope) has a value of1.056-1.071 (n>1), which indicates supercase цtransport diffusion. The results obtained in the present study thus indicate that the polymer and solvents used in the preparation of films have shown significant influence on thewater vapour transmission, drug diffusion and permeability of the films